2018
DOI: 10.1093/ndt/gfy328
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil for the treatment of preeclampsia, an update: should we still be enthusiastic?

Abstract: Preeclampsia is a hypertensive disorder of pregnancy and the clinical manifestation of severe endothelial dysfunction associated with maternal and foetal morbidity and mortality. The primum movens of the disease is the defect of invasion of the uterine arteries by foetal syncytiotrophoblasts, which causes a maladaptive placental response to chronic hypoxia and the secretion of the soluble form of type 1 vascular growth endothelial factor receptor, also called soluble fms-like tyrosine kinase 1 (sFlt-1), the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Others have also reported beneficial blood pressure and/or fetal effects of sildenafil in pregnant hypertensive animals (21,(36)(37)(38)(39)(40)(41)(42). However, these promising pre-clinical data have not translated smoothly into clinical trials (19,43). Earlier studies reported no beneficial effects of sildenafil treatment on pregnancy duration, isolated vessels, or fetal outcomes (22,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also reported beneficial blood pressure and/or fetal effects of sildenafil in pregnant hypertensive animals (21,(36)(37)(38)(39)(40)(41)(42). However, these promising pre-clinical data have not translated smoothly into clinical trials (19,43). Earlier studies reported no beneficial effects of sildenafil treatment on pregnancy duration, isolated vessels, or fetal outcomes (22,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…inhibitor use for these off-label uses is currently sparse, although there are some in vitro and in vivo studies suggesting that PDE5 inhibitor administration may have potential benefits for pre-eclampsia, 23,24 when administered during pregnancy, and wound healing. 25,26 To our knowledge, this was the first study evaluating PDE5 inhibitor use in pregnant and reproductive-age women in the United States using large population-based databases.…”
Section: Discussionmentioning
confidence: 99%
“…These effects could be particularly interesting for maternal or fetal pathology during pregnancy. Sildenafil only modestly reduces blood pressure, granting it a particularly desirable profile for pregnancy where systemic hypotension is deleterious for the fetus [ 7 , 9 ]. Moreover, the hepatic CYP3A4 and CYP2C19 isoenzymes involved in sildenafil’s metabolization were present and active prenatally [ 10 , 11 ].…”
Section: Sildenafilmentioning
confidence: 99%